Assessing the Relationship between Short Birth-to-Pregnancy Interval and the Maternal and Perinatal Outcomes among Multiparous Women in Northern Ghana - Agulu, Gilbert G.; Dzotsi, Emmanuel K.; Issah, Kofi; Nyuzaghl, Josephat A.; Adogboba, Alemna D.; Adongo, Vincent A. (European Scientific Journal, ESJ, 2024)
Introduction: The World Health Organization (WHO) recommends an optimal Birth-to-Pregnancy Interval (BPI) of 24-59 months, or a 33-month interval between two successive births, to reduce the risk of untoward maternal and newborn outcomes. Short Birth to Pregnancy Interval (SBPI) and unmet need for Family Planning (FP) are the major contributors to rapid population growth and increased maternal and newborn mortalities. The purpose of this study was to assess the adverse perinatal and maternal outcomes associated with SBPI among multiparous women in three municipalities of the Upper East Region (UER) of Ghana. Materials and Methods: We employed a cross-sectional design conducted among 904 women aged 15-49 attending Antenatal Care (ANC) clinics in three municipalities in the UER who had at least two successive live births prior to data collection. A multistage cluster sampling technique was employed to recruit respondents for this study. This was conducted in four steps. Out of the 46 health facilities, we randomly selected 25 respondents using the systematic random selection method. Data was collected using a structured questionnaire, incorporated into the electronic data collection tool (Kobo collect), and administered by trained research assistants. Birth interval was categorized according to the WHO’s classification: <24 months as SBPI, 24-≥59 months as Optimal Birth to Pregnancy Interval (OBPI), and >59 months as Long Birth to Pregnancy Interval (LBPI). Results: Of the 904 respondents, the majority (56.2%) had an OBPI, while 36.9% had a SBPI. Factors that influenced SBPI were parity, mode of delivery, and the educational status of woman’s partner. Participants with a higher parity (≥5 children) had 0.67 times the potential of spacing their births (AOR 0.67; 95% CI 0.46-0.98; p = 0.040). Women who experienced a Caesarean Section (CS) delivery were 3.28 times more likely to have LBPI (AOR 3.28; 95% CI 1.02–10.62; p=0.047). Respondents whose partners had secondary education had a 1.87 chance (AOR 2.07; 95% CI 1.09–3.96; p=0.027) of spacing their births. The birth complications reported were retained products of conception (41.9%), pregnancy-induced hypertension (27.9%), postpartum hemorrhage (11.6%), obstructed labor (10.5%), sepsis (38.1%), neonatal jaundice (23.8%), low birth weight (19%), and preterm birth (14.3%). Conclusion: A significant proportion of the participants in this study reported having a short duration between the birth of one child and the conception of the next. This was associated with various adverse maternal and perinatal outcomes, such as birth complications and mortalities. The study emphasizes the need for health professionals to address challenges in contraceptive uptake, especially among multiparous women, and promote optimal birth spacing to improve maternal and perinatal outcomes.